Understanding asparagus tip breakdown postharvest at a molecular and cellular level - Nayakoti, Swapna; Collings, Emma R.; Landahl, Sandra; Chinn, John; Terry, Leon A.; Christofides, Sarah; Alamar, M. Carmen; Rogers, Hilary (International Society for Horticultural Science (ISHS), 2023)
Asparagus has a very limited season in the UK and a short shelf-life. Tip breakdown occurs sporadically during chilled storage and limits shelf-life. It is characterized by internal browning and is accompanied by an unpleasant aroma. The change in aroma can be the first sign of the breakdown, and results in waste as whole batches of asparagus need to be discarded. Data suggest that the breakdown may not be initiated by microbial action, but the underlying mechanisms are yet to be fully elucidated. Tip breakdown occurs more frequently in faster growing spears when growing temperatures are higher. To explore whether the faster growth is associated with larger cells, cell size was compared in spear tips of a cultivar which is more susceptible to tip rot, ‘Aspalim’, and a cultivar in which tip rot very rarely occurs, ‘Early California’. However, no significant differences were found. Transcriptomes were sequenced from healthy spears, and spears in which symptoms of tip breakdown could be seen visually, to assess changes in gene expression during the development of the tip breakdown. More genes were upregulated in spears showing tip breakdown compared to healthy spears after 14 days of chilled storage. The largest functional group of differentially expressed genes is related to DNA binding and transcription regulation which may provide useful information on the overall regulation of the breakdown process.
Keywords: cell size; gene expression; transcriptome